2010
DOI: 10.1088/1468-6996/11/5/055002
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic paper using zinc oxide nanorods

Abstract: Zinc oxide (ZnO) nanorods were grown on a paper support prepared from soft wood pulp. The photocatalytic activity of a sheet of paper with ZnO nanorods embedded in its porous matrix has been studied. ZnO nanorods were firmly attached to cellulose fibers and the photocatalytic paper samples were reused several times with nominal decrease in efficiency. Photodegradation of up to 93% was observed for methylene blue in the presence of paper filled with ZnO nanorods upon irradiation with visible light at 963 Wm -2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(77 citation statements)
references
References 27 publications
1
70
0
1
Order By: Relevance
“…These holes and electrons interact with H 2 O and O 2 , respectively, to yield the OH and OOH hydroxyl radicals; thus, the holes play an important role in photocatalytic reactions. These hydroxyl radicals, which are highly oxidizing in nature, can completely oxidize the dyes by abstracting electron from dye molecules and by breaking the large organic materials into less harmful small organic materials [23,24].…”
Section: Resultsmentioning
confidence: 99%
“…These holes and electrons interact with H 2 O and O 2 , respectively, to yield the OH and OOH hydroxyl radicals; thus, the holes play an important role in photocatalytic reactions. These hydroxyl radicals, which are highly oxidizing in nature, can completely oxidize the dyes by abstracting electron from dye molecules and by breaking the large organic materials into less harmful small organic materials [23,24].…”
Section: Resultsmentioning
confidence: 99%
“…The reason for this is the deceased light penetration, the increased light scattering and the slaughter in surface area occasioned by agglomeration at high solid concentration (Baruah et al 2010). …”
Section: Effect Of Dose Variationmentioning
confidence: 99%
“…Subsequently, past essays have reported that ZnO can decay organic dyes such as methylene blue, Rhodamine B, methyl red and methyl orange under UV irradiation [6][7][8][9][10]. For instance, special attention is focused to promote the photocatalytic activity of ZnO by commanding the size of the particles, concentration of oxygen defects, and surface area.…”
Section: Introductionmentioning
confidence: 99%